Health care experiences for older adults diagnosed with leukemia and lymphoma: Factors associated with emergency department use, timeliness and access of health care. Issue 2 (March 2021) - Fauer, Alex; Wallner, Lauren P.; Davis, Matthew A.; Choi, Sung Won; Friese, Christopher R.
Abstract: Objectives: This study examined the association of ED use in the first year of diagnosis and patient experiences in care among older adults with hematologic malignancies. Materials and Methods: Cross-sectional design using SEER-CAHPS® data from 2002 to 2015 to study Medicare fee-for-service enrollees with a primary diagnosis of leukemia or lymphoma. We linked the CAHPS survey data (patient-reported experiences with health services) to patients' cancer registry information and Medicare outpatient claims from the SEER-CAHPS resource. We estimated associations of ED use and clinical characteristics with two CAHPS outcomes – "getting care quickly" (timeliness) and "getting needed care" (access) – with bivariate and multivariate analyses. Results: The analytic sample included 751 patients, 125 of whom had an ED claim in the first year of cancer diagnosis. The most frequent ED diagnosis clusters were fever and infection ( n  = 17, 13.6%), orthopedic and injury (16, 12.8%) and pain (16, 12.8%). Significantly more enrollees with an ED claim were diagnosed with lymphoma ( p  < 0.01), lived in rural areas (p < 0.01), and lived in areas with many families living in poverty (p < 0.01). In adjusted models, enrollees with an ED claim reported significantly worse access to care ( β  − 4.83; 95%CI -9.29, -0.38; p  = 0.03). Conclusion: The management of urgent care concerns for adults with hematologic malignancies remains an important clinical and quality improvement imperative. Further study is warranted to enhance the management of emergent complications in older adults receiving care for hematologic malignancies, with efforts that enhance coordination of ambulatory oncology care.